2015
DOI: 10.1080/07315724.2015.1005198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sesamin Supplementation on Cardiovascular Risk Factors in Women with Rheumatoid Arthritis

Abstract: Sesamin exhibited a protective effect on cardiovascular risk factors in patients with RA. However, further investigation is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 34 publications
0
55
0
Order By: Relevance
“…To calculate the sample size, we used the standard formula suggested for clinical trials by considering type one error (α) of 0.05 and type two error (β) of 0.20 (power = 80%). The sample size was calculated based on the TAC value 17 . According to this formula, 28 patients per group were needed to complete the study.…”
Section: Methodsmentioning
confidence: 99%
“…To calculate the sample size, we used the standard formula suggested for clinical trials by considering type one error (α) of 0.05 and type two error (β) of 0.20 (power = 80%). The sample size was calculated based on the TAC value 17 . According to this formula, 28 patients per group were needed to complete the study.…”
Section: Methodsmentioning
confidence: 99%
“…In this direction, RA patients with active disease, for example, present with increased levels of ROS and diminished antioxidant potential, ultimately resulting in worse oxidative status for these individuals when compared to healthy controls [13]. Consequently, a greater degree of lipid peroxidation may be found [13,15], either in the synovial fluid or in blood samples from RA individuals [68,69]. Accordingly, serum levels of MDA, a marker of lipid peroxidation, have been described as presenting positive correlation with proinflammatory cytokines in RA [28], with reactive oxygen metabolites (ROM) in blood samples also found to be increased in patients with RA and positively correlated with disease activity [61].…”
Section: Oxidative Stress and Localmentioning
confidence: 99%
“…Several works showed different therapies as efficient complementary alternatives in disease activity control (Table 1) through antioxidant effects, with improvements observed in many disease activity parameters, such as disease activity score-28 joints (DAS-28), erythrocyte sedimentation rate (ESR), health assessment questionnaire-disability index (HAQ-DI), and visual analog scale (VAS). Among them are N-acetylcysteine, used in other diseases due to its antioxidant effect [37], synbiotic supplementation [62], pomegranate extract [66], coenzyme Q10 [70] and sesamin supplementation [68], rectal insufflation of ozone [35], saline balneotherapy [64], and laser acupuncture [69]. For all adjuvant therapies already described in the literature to date, Table 1 shows the route of administration, dose, duration, and other details from each selected study.…”
Section: Antioxidant Therapy In Rheumatoid Arthritismentioning
confidence: 99%
“…Even in the present study we found subjects are predisposed to dyslipidemia condition is invariably. Such controversial report between the studies might be due to duration of study period or co-morbidity of the disease condition or mode of vitamin D exposure 26,27 In conclusion, study reveals that RA has a link with increased prevalence and predisposition of metabolic syndrome. Our study also revealed, among the parameters lipid profile have shown less association with the vitamin D supplementation possibly due to less exposure of sunlight or inadequate intake of vitamin D. While in vitamin D supplementation, disease activity is comparatively less in arthritis patient than in arthritic prediabetic patients.…”
Section: Discussionmentioning
confidence: 93%